Single center experience with ultrasound guided axillary vein port placement. Issue 5 (September 2022) - Tivnan, Patrick; Nannery, Micaela; Epelboym, Yan; Vilvendhan, Rajendran
Purpose: To retrospectively review a single institution experience of ultrasound guided axillary vein port placement. Methods: In this retrospective study, a patient list was generated after searching our internal database from 1/1/2012 to 10/1/2018. Patients who had undergone axillary vein port placement were included. Chart review was performed to confirm approach, laterality and to gather demographic data, clinical indications, technical outcomes, and complications. Descriptive statistics were used to analyze this cohort. Chi-square statistics were used to compare outcomes by laterality. Results: Three hundred seven patients (51% female) with an average age of 58 years were included. The port was placed via the right axillary vein in 85% (261/307), predominantly for the indication of chemotherapy access (296/307). Technical success was achieved in all 307 cases. Peri procedural complications occurred in 1% (4/307) of cases and included port malpositioning requiring replacement and a case of port pocket hematoma. Post procedural complications including deep vein thrombosis and port malfunction occurred in 17% (52/307) of cases and port removal as a result of complication occurred in 9% (29/307) of cases. Conclusions: Ultrasound guided placement of an axillary port is a safe procedure to perform and demonstrates good clinical outcomes.